Binary response Se/ZnO p‐n heterojunction UV photodetector with high on/off ratio and fast speed. Issue 1 (16th December 2016) - Hu, Kai; Teng, Feng; Zheng, Lingxia; Yu, Pingping; Zhang, Zhiming; Chen, Hongyu; Fang, Xiaosheng
Abstract : A UV PD based on Se/ZnO p‐n heterojunction with binary response at small negative bias is presented in this work. At zero bias, the PD shows a high on/off ratio of 10 4 and a fast speed of several milliseconds. The research provides a new path to fabricate ZnO‐based multifunctional and high‐performance UV PDs. Abstract: A high‐performance UV photodetector (PD) based on a p‐Se/n‐ZnO hybrid structure with large area (more than 1×1 cm) is presented in this study. The device is theoretically equivalent to a parallel‐connection circuit for its special structure and shows multifunction at different voltage bias, which means the output signal can be tailored by an applied voltage. The Se/ZnO PD shows binary response (positive and negative current output under on/off periodical light illumination) under small reverse bias (–0.05 V and –0.1 V) which efficiently reduces the negative effect of noise signal in weak‐signal detection applications. At zero bias, with the aid of a p‐n heterojunction, a high on/off ratio of nearly 10 4 is achieved by this device at zero set bias under 370 nm (∼0.85 mW cm −2 ) illumination and this on/off ratio can be achieved in 0.5 s. The device also shows a fast speed with rise time of 0.69 ms and decay time of 13.5 ms measured by a pulse laser, much faster than that of a pure ZnO film. The Se/ZnO PD in this research provides a new pathway to fabricate multifunctional high‐speed, high signal‐to‐noise ratio, high detectivity and high selectivity UV photodetectors.